Investigation of thyroid nodules: A practical algorithm and review of guidelines. Issue 8 (1st April 2018) - Song, Jin Soo A.; Dmytriw, Adam A.; Yu, Eugene; Forghani, Reza; Rotstein, Lorne; Goldstein, David; Poon, Colin S.
Abstract: Background: High resolution ultrasound has led to early detection of subclinical tumors and drastic increase in incidence of thyroid malignancy. To achieve a balance in appropriate investigation without perpetuating an overdiagnosis phenomenon, a concise set of evidence‐based recommendations to stratify risk is required. Methods: We sought to assemble an evidence‐based diagnostic algorithm and accompanying pictorial review for workup of thyroid nodules that summarizes the most recent guidelines. In addition, we conducted a literature search and analysis of our imaging databases. Results: Although many imaging features of benign and malignant nodules can be nonspecific, others, such as microcalcifications, lymphadenopathy, and peripheral invasion, are highly suggestive of malignancy. The predictive values of salient imaging characteristics are presented. Conclusion: Evidence‐based guidelines are available such that a cost‐effective algorithm for thyroid nodule workup can be devised. Conservative management with a focus on periodic monitoring is the working clinical consensus on the approach to thyroid nodules.